Singapura Dilanggar Todak, an interactive E-book - Nabilah Binte Eddy Razali (Nanyang Technological University, 2023)
Introduced in 1960, Singapore’s bilingual policy is intended to promote English as the main language of communication while preserving the use of mother tongue among ethnic races. It is believed that bilingualism is fundamental in strengthening an individual's values and sense of culture as well as promoting cultural harmony and understanding among the different ethnic groups in Singapore. As the current younger generation is being brought up in a world where technology is rapidly becoming essential in the way they learn new things, incorporating tools that make use of these technological advancements is vital in ensuring that students stay engaged.